Historical aspect of international mediation and current trends in its development - M. Zhomartkyzy (Науковий вісник Ужгородського національного університету. Серія Право, 2023)
The article «Historical aspect of international mediation and modern trends of its development» explores the evolution and role of international mediation throughout history and analyzes the current trends of its development in the modern world. The article examines the role of mediation in conflict resolution in different eras, starting from ancient civilizations to the present. Particular attention is paid to key stages in the development of international mediation, such as the Renaissance, the 19th and 20th centuries, and modernity, with a focus on the influence of international organizations and technological innovations. Current trends are also analyzed, including the expansion of actors, the use of modern technology, the increasing role of regional organizations, and cultural sensitivity. The article emphasizes that contemporary international mediation is becoming a more complex and multidimensional phenomenon, playing an important role in conflict resolution and maintaining stability on the world stage.